Rapid on-site nucleic acid testing: On-chip sample preparation, amplification, and detection, and their integration into all-in-one systems - Wang, Jingwen; Jiang, Han; Pan, Leiming; Gu, Xiuying; Xiao, Chaogeng; Liu, Pengpeng; Tang, Yulong; Fang, Jiehong; Li, Xiaoqian; Lu, Chenze (Frontiers in Bioengineering and Biotechnology, 2023)
Nucleic acid testing is playing a vital role in more and more research fields, the need for rapid on-site testing methods is also increasing. The test procedure often consists of three steps, sample preparation, amplification and detection. This review covered recent advances in on chip methods for these three steps and explained the principles of related methods. Sample preparation was further divided into cell lysis and nucleic acid purification and discussed how these two steps were integrated on a single chip. Amplification covered on-chip studies based on PCR and isothermal amplification. Three isothermal amplification methods reported to have good resistance against PCR inhibitors were selected due to their potential in direct amplification. Chip designs and novel strategies to achieve rapid extraction/amplification with satisfying efficiency were discussed. Four detection methods with rapid response (fluorescent, optical and electrochemical detection methods and lateral flow assay) were evaluated regarding their potential in rapid on-site detection. In the last chapter, we discussed how to improve the rapidness of the whole procedure and integrate these three steps on chip, and commented on recent advances and obstacles for lowering the cost of chip manufacture and achieving massive production. We concluded that the future trend would focus on effective nucleic acid extraction with combined methods and direct amplification with isothermal methods.